The efficacy of cognitive behavioral therapy for insomnia in adolescents: a systematic review and meta-analysis of randomized controlled trials - Zhengyang Mei; Chenyi Cai; Shulai Luo; Yuanzhuo Zhang; Chifong Lam; Shi Luo (Frontiers in Public Health, 2024)
ObjectiveThe objective of this systematic review and meta-analysis was to evaluate the overall efficacy of cognitive behavioral therapy for insomnia (CBT-I) in treating insomnia in adolescents, and to examine the efficacy of CBT-I on different sleep-related outcomes in this population.MethodsRandomized controlled trials (RCTs) of CBT-I on insomnia in adolescents were identified using electronic databases and manual searches. The Revised Cochrane risk-of-bias tool for randomized trials (RoB 2) was used to assess risk of bias in RCTs. A standardized mean difference (SMD) with a 95% confidence interval (CI) was used to combine effect sizes. A sensitivity analysis was performed for each outcome using a stepwise elimination method to assess whether the pooled results were significantly affected by individual studies.ResultsThe analysis included 8 RCTs involving a total of 599 participants. The meta-analysis indicated that marked and statistically significant improvements in insomnia (SMD = −1.06; 95% CI -1.65 to −0.47; p < 0.01), sleep onset latency (SMD = −0.99; 95% CI -1.65 to −0.32; p < 0.01), total sleep time (SMD = 0.50; 95% CI 0.10 to 0.90; p = 0.01), and sleep efficiency (SMD = 0.57; 95% CI 0.26 to 0.87; p < 0.01) were observed at post-treatment time point following CBT-I. At follow-up time point, a statistically significant improvement in insomnia (SMD = −0.79; 95% CI -1.42 to −0.17; p = 0.01) was observed following CBT-I.ConclusionCBT-I was effective in improving insomnia in adolescents and some sleep-related outcomes, including sleep onset latency, total sleep time, and sleep efficiency. CBT-I was characterized by low risk and high therapeutic benefits and could serve as alternative or adjuvant approaches to medication for the treatment of insomnia. Considering the advantages in terms of safety and efficacy, CBT-I should be the preferred intervention for the treatment of insomnia in adolescents.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, CRD42024526102.